Sabotaged : dreams of utopia in Texas - Pratt, James, 1927- (University of Nebraska Press, 2020)
"Sabotaged is the account of French, Swiss, and Belgian intellectuals who followed Victor Considerant to Texas in 1855 in a quixotic attempt to fulfill their dreams of a new life in a utopia"--